1985
DOI: 10.1136/bmj.290.6461.13
|View full text |Cite
|
Sign up to set email alerts
|

Natural progesterone and antihypertensive action.

Abstract: In a placebo controlled, double blind crossover study natural progesterone was given by mouth, in increasing doses, to six men and four postmenopausal women with mild to moderate hypertension who were not receiving any other antihypertensive drugs. When compared with values recorded before treatment and during administration of placebo progesterone caused a significant reduction in blood pressure, suggesting that progesterone has an antihypertensive action rather than a hypertensive one as has been previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
3
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 3 publications
3
50
3
3
Order By: Relevance
“…[40][41][42]44 In contrast to the vasoconstrictor effects observed with the 'androgenic' progestogens, the 'non-androgenic' progestogens including progesterone and medroxyprogesterone (which was used in the current study) have been shown to have a net vasodilator effect. 38,41,44 The observations in the present study examining the dose-response of cyclical MPA in the presence of a fixed replacement dose of oestrogen are consistent with MPA having either no net effect on vascular tone or a small net vasodilator effect. The mechanisms of the effect of the different progestogens on the vasculature remain unclear and warrant further investigation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…[40][41][42]44 In contrast to the vasoconstrictor effects observed with the 'androgenic' progestogens, the 'non-androgenic' progestogens including progesterone and medroxyprogesterone (which was used in the current study) have been shown to have a net vasodilator effect. 38,41,44 The observations in the present study examining the dose-response of cyclical MPA in the presence of a fixed replacement dose of oestrogen are consistent with MPA having either no net effect on vascular tone or a small net vasodilator effect. The mechanisms of the effect of the different progestogens on the vasculature remain unclear and warrant further investigation.…”
Section: Discussionsupporting
confidence: 79%
“…31,[36][37][38] Contraceptive preparations tend to differ from 'postmenopausal replacement' regimens in that they consist of combinations of the 'potent' semisynthetic oestrogens ethinyloestradiol or mestranol, often with the relatively androgenic C19 progestogens, both administered in doses in excess of those used in HRT. 60 The relatively higher doses and potency of the preparations used in oral contraceptive formulations may therefore influence the effects on the vasculature and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In vivo administration of oestrogen or natural progesterone can bring about an acute drop in blood pressure. 5,6 In hypertensive women a number of small studies have documented an antihypertensive effect. Transdermal oestradiol can reduce daytime systolic pressure, 7 achieve an absolute reduction in overall pressures 8 and restore a normal 24-h ambulatory blood pressure profile.…”
Section: Discussionmentioning
confidence: 99%
“…4 Little information is available regarding the long-term effects of HRT in hypertensive women, but short duration studies in hypertensive women have demonstrated either a neutral or even modest hypotensive effect. [5][6][7][8][9][10] Cyclical HRT preparations are unacceptable to most women suffering from coronary disease or hypertension. Tibolone is a novel steroid compound, which controls menopausal symptoms, 11 inhibits postmenopausal bone loss 12 and augments forearm blood flow.…”
Section: Introductionmentioning
confidence: 99%